2006
DOI: 10.4049/jimmunol.176.10.6323
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 Suppresses Autoimmune Retinal Disease by Promoting Concomitant Th2- and T Regulatory-Mediated Anti-Inflammatory Responses

Abstract: Intraocular inflammatory diseases are a common cause of severe visual impairment and blindness. In this study, we investigated the immunoregulatory role of galectin-1 (Gal-1), an endogenous lectin found at sites of T cell activation and immune privilege, in experimental autoimmune uveitis (EAU), a Th1-mediated model of retinal disease. Treatment with rGal-1 either early or late during the course of interphotoreceptor retinoid-binding protein-induced EAU was sufficient to suppress ocular pathology, inhibit leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
153
2
16

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(192 citation statements)
references
References 61 publications
5
153
2
16
Order By: Relevance
“…We found that treatment with recombinant galectin-1 in the efferent phase of autoimmune ocular inflammation results in increased IL-10 and TGF-β production and expansion of regulatory T cells in vivo [43]. Interestingly, recent studies demonstrated that galectin-1 and -10 are overexpressed in regulatory T cells, and are critical for the suppressive activity of these cells [49,50].…”
Section: Galectin-glycoprotein Lattices In T Cell Functionsmentioning
confidence: 83%
See 1 more Smart Citation
“…We found that treatment with recombinant galectin-1 in the efferent phase of autoimmune ocular inflammation results in increased IL-10 and TGF-β production and expansion of regulatory T cells in vivo [43]. Interestingly, recent studies demonstrated that galectin-1 and -10 are overexpressed in regulatory T cells, and are critical for the suppressive activity of these cells [49,50].…”
Section: Galectin-glycoprotein Lattices In T Cell Functionsmentioning
confidence: 83%
“…Compelling evidence indicates that galectin-1 treatment suppresses chronic inflammation, modulates T-cell survival and skews the balance towards a Th2 cytokine profile in vitro [42] and in vivo in animal models, including experimental autoimmune uveitis [43] and autoimmune diabetes [44]. Furthermore, selective blockade of galectin-1 in tumor tissue results in increased Th1-mediated anti-tumor responses, suggesting potential involvement of this protein in tumorimmune escape [45].…”
Section: Galectin-glycoprotein Lattices In T Cell Functionsmentioning
confidence: 99%
“…However the intracellular form of this protein has not been implicated in the process of apoptosis. Since Gal-1 has been proposed as a possible candidate for immunosuppressive therapy in earlier studies [8,11,13,33], we turned to the prototypical inflammatory autoimmune disease, SLE as a pathological model. Our results showed that active SLE T-cells contained significantly lower levels of Gal-1 mRNA than healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous gal-1 has immunosuppressive and anti-inflammatory effects in experimental models of inflammation and autoimmunity such as inflammatory bowel disease, autoimmune retinal disease, autoimmune diabetes, and collagen-induced arthritis [5][6][7][8]. In addition, gal-1-deficient mice show augmented Th1 and Th17 responses and enhanced susceptibility to autoimmune neuroinflammation [3].…”
Section: Introductionmentioning
confidence: 99%